2008
DOI: 10.1577/a06-042.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chloramine‐T to Control Mortality in Freshwater‐Reared Salmonids Diagnosed with Bacterial Gill Disease

Abstract: Bacterial gill disease (BGD), caused by Flavobacterium branchiophilum and other species of yellow‐pigmented, filamentous bacteria, is a common and potentially catastrophic disease of hatchery (freshwater)‐reared fish. Chloramine‐T (Chl‐T) is a biocide proven effective for controlling mortality in freshwater‐reared fish diagnosed with BGD. However, Chl‐T is not approved by the U.S. Food and Drug Administration for such use. To generate data in support of a U.S. approval, we evaluated the effectiveness of Chl‐T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
0
9
0
3
Order By: Relevance
“…Hypochlorite ions that form *Corresponding author: jim bowker@fws.gov Received March 16, 2015;accepted May 10, 2015 when CLT is dissolved in water (Booth and McDonald 1988) are strong oxidizers that can quickly destroy cellular material and disrupt essential cell processes (Powell and Clark 2003). Chloramine-T has been shown to effectively control the mortality associated with bacterial gill disease (BGD) in salmonids 525 (from 1980;Speare and Ferguson 1989;Bullock et al 1991; Thorburn and Moccia 1993;Ostland et al 1995;Bowker and Erdahl 1998;Bowker et al 2008b) and with external columnaris in Largemouth Bass Micropterus salmoides and Bluegill Lepomis macrochirus (Bowker et al 2013). The toxicity of CLT to fishes has also been investigated (Bills et al 1988;Powell et al 1995Perry 1996, 1998;Sanchez et al 1996Sanchez et al , 1997King and Farrell 2002;Powell and Harris 2004;Gaikowski et al 2008Gaikowski et al , 2009Bowker et al 2011), with results indicating an adequate margin of safety when it is used according to established treatment protocols.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypochlorite ions that form *Corresponding author: jim bowker@fws.gov Received March 16, 2015;accepted May 10, 2015 when CLT is dissolved in water (Booth and McDonald 1988) are strong oxidizers that can quickly destroy cellular material and disrupt essential cell processes (Powell and Clark 2003). Chloramine-T has been shown to effectively control the mortality associated with bacterial gill disease (BGD) in salmonids 525 (from 1980;Speare and Ferguson 1989;Bullock et al 1991; Thorburn and Moccia 1993;Ostland et al 1995;Bowker and Erdahl 1998;Bowker et al 2008b) and with external columnaris in Largemouth Bass Micropterus salmoides and Bluegill Lepomis macrochirus (Bowker et al 2013). The toxicity of CLT to fishes has also been investigated (Bills et al 1988;Powell et al 1995Perry 1996, 1998;Sanchez et al 1996Sanchez et al , 1997King and Farrell 2002;Powell and Harris 2004;Gaikowski et al 2008Gaikowski et al , 2009Bowker et al 2011), with results indicating an adequate margin of safety when it is used according to established treatment protocols.…”
mentioning
confidence: 99%
“…As part of the effort to obtain FDA approval of the use of CLT in U.S. aquaculture, researchers at the U.S. Fish and Wildlife Service (FWS) Aquatic Animal Drug Approval Partnership program conducted CLT efficacy (EFF) studies on Rainbow Trout Oncorhynchus mykiss, Apache Trout O. apache, and Chum Salmon O. keta (Bowker et al 2008b), and target animal safety (TAS) studies on Rainbow Trout (Bowker et al 2011). Though all CLT doses administered in these studies were analytically verified and found to be within FDA-acceptable limits (i.e., target dose ± 25%), all had been administered in standing-bath treatment conditions.…”
mentioning
confidence: 99%
“…Chloramine-T (C 7 H 7 ClNNaO 2 S·3H 2 O) is a biocide used worldwide as a disinfectant and antiseptic. Although CLT has been used for years under authorization of publically held Investigational New Animal Drug (INAD) exemptions and has been shown to effectively control mortality associated with BGD in freshwater-reared salmonids (From 1980;Speare and Ferguson 1989;Bullock et al 1991;Thorburn and Moccia 1993;Ostland et al 1995;Bowker and Erdahl 1998;Bowker et al 2008) and columnaris in a variety of freshwater finfish, it is not yet approved by the U.S. Food and Drug Administration (FDA) for use on fish.…”
mentioning
confidence: 99%
“…Consequently, efforts have been underway for many years to obtain a NADA for CLT for use in U.S. aquaculture to control mortality in freshwater-reared finfish caused by bacterial gill disease (BGD; causative agent, Flavobacterium branchiophilum) and other external flavobacterial infections. Chloramine-T effectively controls BGD-related mortality in salmonids (From 1980;Speare and Ferguson 1989a;Bullock et al 1991; Thorburn and Moccia 1993;Ostland et al 1995;Bowker and Erdahl 1998;Bowker et al 2008). The toxicity of CLT to fishes has also been investigated (Bills et al 1988;Powell et al 1994Powell et al , 1995Perry 1996, 1998;Sanchez et al 1996Sanchez et al , 1997King and Farrell 2002;Powell and Harris 2004); however, these studies were not designed to meet current FDA TAS testing requirements (USFDA Center for Veterinary Medicine 1989Medicine , 1999.…”
mentioning
confidence: 99%
“…For salmonids, the proposed CLT treatment regimen is to administer the drug at 12-20 mg/L in a static or flow-through bath for 60 min/d on three alternate or consecutive days (Bowker et al 2008). To evaluate the safety of this proposed treatment regimen, we conducted eight TAS experiments with CLT on a representative salmonid, rainbow trout Oncorhynchus mykiss.…”
mentioning
confidence: 99%